2022
DOI: 10.30574/gscarr.2022.12.1.0190
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between environmental innovation, energy efficiency and environmental sustainability in the lower-income economy

Abstract: Every major event on a national or global scale influences the environment, and scientists are always looking for new solutions to decrease ecological destruction. Throughout the preceding decade, professionals offered and executed policy ideas for energy adaptation and integration, such as the use of renewable energy. Between 1980 and 2021, the study looks at the relationship between environmental innovation, energy efficiency, and institutional quality in low-income nations. Autoregressive distributed lag (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…It has been shown that elevating the level of financial transparency a company presents positively impacts the business's overall success and is advantageous to the organization as a whole. Performance may be defined in terms of the business's profit margin, rate, or return on assets; alternatively, it may be assessed in terms of a rise in the company's stock value (Andrimahery and Qamruzzaman, 2022b;Liang & Qamruzzaman, 2022;Ma & Qamruzzaman, 2022). Alternatively, this performance may be measured in terms of the increase in the company's overall value.…”
Section: Financial Disclosure Quality and Firm's Performancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that elevating the level of financial transparency a company presents positively impacts the business's overall success and is advantageous to the organization as a whole. Performance may be defined in terms of the business's profit margin, rate, or return on assets; alternatively, it may be assessed in terms of a rise in the company's stock value (Andrimahery and Qamruzzaman, 2022b;Liang & Qamruzzaman, 2022;Ma & Qamruzzaman, 2022). Alternatively, this performance may be measured in terms of the increase in the company's overall value.…”
Section: Financial Disclosure Quality and Firm's Performancementioning
confidence: 99%
“…NCEThe total number of committees a firm has Award 1 mark if the committee established in the firm i in year t is greater than the median value of the sample in a specific industry, 0 mark otherwise(Crane et al, 2016) Dividend payment DP Measured by the dividend per share Award 1 mark if the dividend paid in the firm i in year t is greater than the median value of the sample in a specific industry, 0 marks otherwise(Easterbrook & Fischel, 1984;Qamruzzaman, 2022b) Three control variables that may affect firm performance are added to the sample: FIRM SIZE, measured by the natural logarithm of total assets; LEVERAGE, measured by the ratio of total debts to total assets; and FIRM AGE, measured by the number of operating years since establishment. For details, see Table2.…”
mentioning
confidence: 99%
“…Increasing numbers of empirical research [38,39] have pointed the finger at energy use as the primary cause of environmental deterioration. Accelerating economic development at the expense of the environment results from reliance on traditional energy sources beyond their limits [40][41][42][43][44][45][46] In Rahman [47] study, he takes 10 of the highest electricity-consuming nations during 192-2013 to explore the relationship between energy use, economic development, and the destruction of the world environment. According to a recent study, the environmental deterioration rate is accelerated by using energy.…”
Section: Environmental Degradation and Energy Consumptionmentioning
confidence: 99%
“…Increasing numbers of empirical research [22][23][24][25][26] have pointed the finger at energy use as the primary cause of environmental deterioration. Accelerating economic development at the expense of the environment results from reliance on traditional energy sources beyond their limits [27]. In Rahman's [28] study, he takes 10 of the highest electricity-consuming nations during 192-2013 to explore the relationship between energy use, economic development, and the destruction of the world environment.…”
Section: Environmental Degradation and Energy Consumptionmentioning
confidence: 99%